Description of Students' Learning and Innovation Skills in Global Warming Learning Class X SMA Penggerak - Dwi Shinta Anggraini; Zonalia Fitriza (Universitas Riau, 2023)
The 21st century is known as the century of knowledge that experiences rapid changes, to deal with it a skill is needed. One of the 21st century skills is learning and innovation skills or known as 4Cs, namely Communication, Collaboration, Critical Thinking and Problem-Solving, Creativity and Innovation. Students' 4Cs skills are highly demanded during the learning process, so it is important to assess students' 4Cs skills. Global warming is one of the chemistry subject matter in the penggerak school curriculum. This type of research is descriptive research with a qualitative approach. The study aims to describe the 4C skills of students in class XE7 SMA Negeri 2 padang with a total of 30 students. This study used an observation sheet. The results showed that overall the communication skills of students in class XE7 SMA Negeri 2 Padang were on average classified in the incompetent category (55% of students), students' collaboration skills were classified in the competent category (42% of students), students' critical thinking and problem-solving skills were classified in the incompetent category (40% of students), and creativity and innovation skills were classified in the incompetent category (88% of students).